Effectiveness of technology-enhanced simulation in teaching digital rectal examination: a systematic review narrative synthesis. (1st September 2020) - Al Asmri, Mansour A; Ennis, James; Stone, Robert John; Bello, Fernando; Haque, M Sayeed; Parle, Jim
Abstract : Background: Digital rectal examination (DRE) is a challenging examination to learn. Objective: To synthesise evidence regarding the effectiveness of technology-enhanced simulation (TES) for acquiring DRE skills. Study selection: EMBASE, Medline, CINAHL, Cochrane, Web of Knowledge (Science and Social Science), Scopus and IEEE Xplore were searched; the last search was performed on 3 April 2019. Included were original research studies evaluating TES to teach DRE. Data were abstracted on methodological quality, participants, instructional design and outcomes; a descriptive synthesis was performed. Quality was assessed using a modified Medical Education Research Study Quality Instrument. The study design domain was modified by scoring the papers based on (1) evaluation of risk of bias for randomised controlled trials, (2) description of participants and (3) assessment of robustness and degree of simulation fidelity of the assessments used to evaluate learning. Findings: 863 articles were screened; 12 were eligible, enrolling 1507 prequalified medical/clinical students and 20 qualified doctors. For skill acquisition, role player was statistically significantly superior to a static manikin (2 studies). For knowledge acquisition, manikin use was significantly superior to role player (1 study); 2 studies showed no difference. For confidence, manikin use was significantly superior to no manikin (4 studies). For comfort, manikin use was significantly superior to no manikin (2 studies). For anxiety, role player was significantly superior to manikin (1 study). Median overall quality score (QS) was 48% (27–62). Highest median QS was 73% (33–80) for data analysis; lowest median QS was 20% (7–40) for the validity of instrument. Six papers scored over 50% of the maximum score for overall quality. Conclusions: TES training is associated with improved DRE skills and should be used more widely.